Peculiarities of the English Legal Text Discourse: The Issues of Interpretation and Translatability - Bobrova, Natalia E.; Lebedev, Anton V.; Pinkovetskaia, Iuliia S. (Journal of History Culture and Art Research, 2020)
The growth of international cooperation, trade, tourism and emigration arouses the interest of both linguists and legal experts in the theory and practice of legal translation. The existing difference in the laws of countries, basic features typical of Russian and English legal discourse should be taken into account when dealing with juridical texts. The issue of adequate transfer of the content of legal documents is of importance when translating from one language to another. To identify the basic features typical of the English juridical vocabulary and to offer a methodology for solving the problems occurring when translating juridical texts, the authors implement the methods of syntactic, vocabulary, comparative and comparative translation analysis. The studied material is certain lexemes (commonly used words, terminology, professionalisms, Latinisms, abbreviations and idioms), legal texts (court rulings, legal contracts, official business documents) taken from the authentic British and American legal sources as well as examples from the authors’ translation and teaching practices. The authors believe that a retrospective analysis of conditions contributing to Legal English historic development will facilitate sufficient comprehension of subject areas constituting legal discourse. The findings indicate that the difference between the Russian and English juridical lexemes is conditioned by both linguistic and extra-linguistic factors.